A shackled revolution? The Bubble Act and financial regulation in 18th century England - William McColloch (The University of Utah, Department of Economics, 2013)
Revisionist estimates of growth rates during the British industrial revolution, though largely successful in presenting a more modest picture of Britain's 'take-off' prior to the 1830s, have also posed fresh analytical difficulties for champions of the new economic history. If 18th-century Britain was witness to a diffuse explosion of 'useful knowledge', why did aggregate growth rates or industrial output growth rates not more closely shadow the pace of technological change? In effort to explain this paradox, Peter Temin and Hans-Joachim Voth have claimed that a few key institutional restrictions on financial markets - namely the Bubble Act, and tightening of usury laws in 1714 - served to amplify the crowding out impact of government borrowing. Against this vision, the present paper contends that the adverse impact of financial regulation and state borrowing in 18th century Britain has been greatly overstated. To this end, the paper first briefly outlines the historical context in which the Bubble Act emerged, before turning to survey the existing diversity of perspectives on the Act's lasting impact. It is then argued that there is little evidence to support the view that the Bubble Act significantly restricted firms' access to capital. Following this, it is suggested that the crowding out model, theoretical shortcomings aside, is largely inapplicable to 18th century Britain. The savings-constrained vision of British capital markets significantly downplays the extent to which the Bank of England, though founded as an institution to manage the public debt, provided the entire financial system with liquidity in the 18th century.
Keywords: N13; N23; O43; E44; 330; Bubble Act; Bank of England; Financial Regulation; Industrialization